2018
DOI: 10.1503/cmaj.171076
|View full text |Cite
|
Sign up to set email alerts
|

Ecological association between operative vaginal delivery and obstetric and birth trauma

Abstract: T he increase in cesarean delivery over the past several decades has occurred concomitantly with a decline in operative vaginal deliveries. In the United States, operative vaginal delivery rates decreased from 9.4% in 1995 to 3.1% of all deliveries in 2015, whereas cesarean delivery rates increased from 20.8% to 32.0%.1,2 In Canada as well, rates of operative vaginal delivery followed the same downward trajectory, from 16.8% of all vaginal deliveries in 1995 to 13.2% in 2014, 3,4 whereas cesarean delivery rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 17 publications
8
35
0
1
Order By: Relevance
“…IVD rates close to Western European countries are reported from other overseas high-income nations such as Australia (11%) and Canada (10.7%) 45 . Whilst in the UK the rates of IVD have remained relatively stable (10–13%) over the years, in North America it is considered a declining practice, especially in the USA 30,46,47 , where the IVD rate notably decreased from 9.4% in 1995 to 3.1% in 2017, and the CS rate considerably increased from 20.8% in 1995 up to 32.0% in 2017 46,48–50 . The decrease in the IVD rate was less prominent in Canada, but still decreased from 16.8% of all VD in 1995 to 13.2% in 2014, with the CS rate increasing from 17.6% up to 27.3% 46,51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IVD rates close to Western European countries are reported from other overseas high-income nations such as Australia (11%) and Canada (10.7%) 45 . Whilst in the UK the rates of IVD have remained relatively stable (10–13%) over the years, in North America it is considered a declining practice, especially in the USA 30,46,47 , where the IVD rate notably decreased from 9.4% in 1995 to 3.1% in 2017, and the CS rate considerably increased from 20.8% in 1995 up to 32.0% in 2017 46,48–50 . The decrease in the IVD rate was less prominent in Canada, but still decreased from 16.8% of all VD in 1995 to 13.2% in 2014, with the CS rate increasing from 17.6% up to 27.3% 46,51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst in the UK the rates of IVD have remained relatively stable (10–13%) over the years, in North America it is considered a declining practice, especially in the USA 30,46,47 , where the IVD rate notably decreased from 9.4% in 1995 to 3.1% in 2017, and the CS rate considerably increased from 20.8% in 1995 up to 32.0% in 2017 46,48–50 . The decrease in the IVD rate was less prominent in Canada, but still decreased from 16.8% of all VD in 1995 to 13.2% in 2014, with the CS rate increasing from 17.6% up to 27.3% 46,51,52 . As mentioned in the introduction, declining IVD rates generally correspond to increasingly higher CS rates, and an increased use of IVD has been recommended as one of the strategic approaches to contain the recourse to unnecessary CS 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Addition ally, the study by Janssen and colleagues included deliveries from 15 to 20 years ago, when rates of obstetric anal sphincter injury were significantly lower. 5 Klein and Kaczorowski appear to have missed the main conclusion of our study, which showed a) that episiotomy use in Canada has declined among both sponta neous and operative vaginal deliveries and b) that episiotomy use in spontaneous vag inal deliveries increases the risk of obstet ric anal sphincter injury, while episiotomy use in operative vaginal deliveries protects against obstetric anal sphincter injury. The finding that episiotomy use increases risk of obstetric anal sphincter injury in sponta neous vaginal deliveries has been docu mented in several randomized trials 6 and is not under debate: the guideline from The Society of Obstetricians and Gynaecolo gists of Canada 7 on the use of episiotomy in spontaneous vaginal delivery already reflects the evidence.…”
mentioning
confidence: 61%
“…Linked research by Young and colleagues 2 and Muraca and colleagues 3 provide Canadian data to fuel this discussion. Both studies are well-designed, large database studies evaluating, respectively, the safety of trial of vaginal delivery after previous cesarean birth and the risk of harms from operative vaginal delivery in women with and without a previous cesarean birth.…”
mentioning
confidence: 97%
“…These findings compel us to evaluate whether a goal of reducing our cesarean delivery rate could come at too high a cost to our patients. Muraca and colleagues' most recent work, 3 as well as their previous study looking at trauma rates associated with mid-pelvic operative deliveries, 4 have shown that the use of operative vaginal delivery is associated with startlingly high rates of severe perineal trauma.…”
mentioning
confidence: 99%